2014
DOI: 10.1016/j.canlet.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a long non-coding RNA (CCAT1) in living cells and human adenocarcinoma of colon tissues using FIT–PNA molecular beacons

Abstract: Although the function and mechanism of action of long non-coding RNAs (lncRNA) is still not completely known, studies have shown their potential role in the control of gene expression and regulation, in cellular proliferation and invasiveness at the transcriptional level via multiple mechanisms. Recently, colon cancer associated transcript 1 (CCAT1) lncRNA was found to be expressed in colorectal cancer (CRC) tumors but not in normal tissue. This study aimed to study the ability of a CCAT1-specific peptide nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 45 publications
1
75
1
Order By: Relevance
“…LncRNA-H19 can increase cell invasion and metastasis in bladder cancer through associating with EZH2 and inhibiting E-cadherin (19), while LncRNA-EBIC is found to promote tumor invasion by similar mechanism in cervical cancer (18). Aberrant expressed lncRNAs also unravelled their importance in CRC (20)(21)(22)(23)(24)(25). However, most of lncRNA studies focused on correlations of clinicopathological characteristics and prognosis, the mechanisms are rarely clarified, especially for mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-H19 can increase cell invasion and metastasis in bladder cancer through associating with EZH2 and inhibiting E-cadherin (19), while LncRNA-EBIC is found to promote tumor invasion by similar mechanism in cervical cancer (18). Aberrant expressed lncRNAs also unravelled their importance in CRC (20)(21)(22)(23)(24)(25). However, most of lncRNA studies focused on correlations of clinicopathological characteristics and prognosis, the mechanisms are rarely clarified, especially for mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large quantity of lncRNAs have been identified and studies on the biological functions of lncRNAs on various kind of human cancers have been exponentially growing [96,97]. Although many key questions about lncRNAs remain unsolved, exploration on lncRNAs field gives us a better understanding on cancer diagnosis and treatment.…”
Section: Future Perspectivementioning
confidence: 99%
“…Accordingly, a plasmid composed of the H19 gene regulatory element that drives the expression of diphtheria toxin (DT-A) gene has been developed and it is undergoing clinical testing as a treatment for CRC and other cancers [103,104]. Moreover, Kam and colleagues [105] showed that a well designed peptide nucleic acid (PNA)-molecular beacon (PNA-MB) complementary to lncRNA-CCAT1 can be used as a tool for imaging cell lines and detecting malignancies in human CRC biopsies in situ, indicating the potential diagnostic application of lncRNAs in CRC. Taken together, although the research of lncRNAs is presently at its infancy and only a small number of lncRNAs have been characterized, dysregulated lncRNAs in CRC could still become an important factor for both the diagnosis and prognosis of CRC.…”
Section: Potential Clinical Applications Of Lncrnas In Crcmentioning
confidence: 99%